Deep preferential trade agreements and upgrading in global value chains: the case of Vietnam - Axel Berger; Dominique Bruhn; Andrea Bender; Julia Friesen; Katharina Kick; Felix Kullmann; Robert Roßner; Svenja Weyrauch (Deutsches Institut für Entwicklungspolitik (DIE), 2016)
How and to what extent can deep preferential trade agreements (PTAs) support the upgrading of companies from developing countries within global value chains (GVCs)? This question is of increasing importance, as PTAs have become the trade instrument of choice of major trading powers, and their contents regulate policy areas that could potentially interfere with national development strategies. This study focusses on Vietnam, which aims both at moving beyond low value-added production activities in GVCs and increasing economic integration by signing deep PTAs such as the Trans-Pacific Partnership and the EU–Vietnam Free Trade Agreement. Based on empirical evidence from a new business survey, interviews with stakeholders in Vietnam and the analysis of key PTA provisions, we find that deep PTAs can provide new opportunities for Vietnamese firms to upgrade in GVCs – either directly, by providing concrete incentives for upgrading, or indirectly, by addressing some of the identified barriers for upgrading. However, this potential will not materialise automatically and requires both a strategic vision and support programmes initiated by the government and business associations. The findings of this study are relevant not only for Vietnam, but also for a range of other middle-income countries that aim at achieving upgrading in GVCs and may face the decision to sign deep PTAs with major trading powers.
Keywords: 330; Strukturwandel; wirtschaftliche Entwicklung und Beschäftigung; Handel und Investitionen